Basic symptoms in offspring of parents with mood and psychotic disorders. Issue 4 (July 2019) - Zwicker, Alyson; MacKenzie, Lynn E.; Drobinin, Vladislav; Howes Vallis, Emily; Patterson, Victoria C.; Stephens, Meg; Cumby, Jill; Propper, Lukas; Abidi, Sabina; Bagnell, Alexa; Schultze-Lutter, Frauke; Pavlova, Barbara; et al.
Abstract : Background: Basic symptoms, defined as subjectively perceived disturbances in thought, perception and other essential mental processes, have been established as a predictor of psychotic disorders. However, the relationship between basic symptoms and family history of a transdiagnostic range of severe mental illness, including major depressive disorder, bipolar disorder and schizophrenia, has not been examined. Aims: We sought to test whether non-severe mood disorders and severe mood and psychotic disorders in parents is associated with increased basic symptoms in their biological offspring. Method: We measured basic symptoms using the Schizophrenia Proneness Instrument – Child and Youth Version in 332 youth aged 8–26 years, including 93 offspring of control parents, 92 offspring of a parent with non-severe mood disorders, and 147 offspring of a parent with severe mood and psychotic disorders. We tested the relationships between parent mental illness and offspring basic symptoms in mixed-effects linear regression models. Results: Offspring of a parent with severe mood and psychotic disorders ( B = 0.69, 95% CI 0.22–1.16, P = 0.004) or illness with psychotic features ( B = 0.68, 95% CI 0.09–1.27, P = 0.023) had significantly higher basic symptom scores than control offspring. Offspring of a parent with non-severe mood disorders reported intermediate levels of basic symptoms, that did not significantly differ from control offspring. Conclusions: Basic symptoms during childhood are a marker of familial risk of psychopathology that is related to severity and is not specific to psychotic illness. Declaration of interest: None.